NOVO SÍTIO DE OCORRÊNCIA DE Coquillettidia (Rhynchotaenia) albifera (Prado, 1931) (DIPTERA: CULICIDAE) - Gil-Santana, Hélcio R.; Zeraik, Soraya O. (Revista de Patologia Tropical / Journal of Tropical Pathology, 2011)
A new site of occurrence of Coquillettidia (Rhynchotaeniaj albifera (Prado 1931) (Diptera: Culicidae). The occurrence of Coquilleiiidia <R.) albifera ín the state of Rio de Janeiro, Brazil is herein registered for the first time in the literature